Legitimacy in international society - Clark, Ian, 1949- (Oxford University Press, 2005)
Policy makers and publics alike regularly debate the legitimacy of international events, such as the war on terror, or war in Iraq. But what exactly does legitimacy mean in an international setting? This work provides a grounded analysis of this critical issue in contemporary society.